Intergroup bias and perceived similarity: Effects of successes and failures on support for in- and outgroup political leaders. (January 2013) - Alabastro, Alexis; Rast, David E.; Lac, Andrew; Hogg, Michael A.; Crano, William D.
Drawing on the social identity theory of leadership and optimal distinctiveness theory, this research examined differences in perceived attitude similarity to in- and outgroup leaders among Liberals and Conservatives before and after the 2008 U.S. presidential election. We predicted Liberals and Conservatives alike would perceive their ingroup leaders (Obama or McCain) to be attitudinally similar to themselves before the election. After the election, however, Conservatives were expected to distance themselves from McCain and to accentuate similarity to Obama. Using a longitudinal design, analysis of American National Election Survey ( N = 742) data showed that Liberals and Conservatives viewed themselves to be similar to their respective ingroup leader and dissimilar to the outgroup leader. Consistent with expectations, Conservatives significantly accentuated perceived similarity with Obama following his electoral victory, and significantly distanced themselves from McCain following his loss. Liberals' similarity with either candidate did not change from pre- to postelection. Implications for social identity in inter- and intragroup leadership contexts are discussed.